Batteries & Supercaps: Beyond Lithium‐Ion Batteries. Issue 7 (31st May 2021) - Hasa, Ivana; Adelhelm, Philipp; Cao, Guozhong; Mai, Liqiang
Abstract : The next best thing : In this Editorial, we present the body of work of this Special Collection, which aims at highlighting the dynamic research environment surrounding the next‐generation electrochemical energy storage technologies, bringing together the latest research conducted on "beyond lithium‐ion batteries".